C-type hypertension: An ignored new killer? - Chun-Song Hu (Cardiology Plus, 2017)
In this paper, the authors introduced a kind of hypertension called “C-type Hypertension (CtH)” which is related to “a new type of stress” caused by unhealthy lifestyles. Unlike H-type hypertension caused by an elevated serum level of Hcy, the clinical feature was found to cause a temporary remarkable increase or continually slow increase in the level of human cortisol, the standard biomarker of CtH. This kind of hypertension often appears among young- or middle-age people and may present as a new killer which may result in acute myocardial infarction, acute or chronic heart failure, stroke, or sudden cardiac death.